Fenomena Kehidupan Keturunan Eks Partai Komunis Indonesia Di Kabupaten Banyuwangi Tahun 2018 - Mundir Mundir (IAI Darussalam, 2019)
This type of phenomenological qualitative research intends to explore and describe the religious, social and cultural life of people descended from the former Indonesian Communist Party (PKI) in the Banyuwangi Regency. By analyzing interactive model data, the following research results are obtained. First, the religious life of the former PKI religious community is similar to those of other religions. They mostly acknowledged that the involvement of their parents and grandparents in the PKI was only due to ignorance and because of economic factors. Secondly, the social life of former PKI descendants in Banyuwangi was normal, even though there was something abnormal. While from the aspect of their work many works as teachers, farmers or private and participate in the transmigration program. Third, the cultural life of the descendants of former PKI members in the Banyuwangi Regency exists in developing the culture and arts of Banyuwangi, such as ketoprak, puppet people, ludruk, ande-ande moss, angklung, and keroncong. Art for them is an expression and freedom in conveying ideas through music and art.